Effectiveness of RFID Technology in Library Management System in Bangladesh - Mostafizur Rahman, Md. (Indian Journal of Information Sources and Services, 2019)
The purpose of the study is to evaluate the effectiveness of Radio Frequency Identification (RFID) technology in library management system and services in Bangladesh. This study followed survey and interview methods of data collection through a structured questionnaire. The population of study was all nine libraries in Bangladesh where RFID technology has been installed. The study reveals that all nine libraries are using RFID technology, namely, anti-theft detection Electronic Article Surveillance (EAS) gate, staff-work station and RFID tag. In addition to these, some of them are using kiosk, converter, level printer, book drop station, digital library assistance (DLA) and RFID smart card for entrance. The significance numbers of library users employ the RFID system and services and it is increasing gradually, but some of the RFID machines like level printer, book drop station and DLA are under-utilized because of lack of trained staff, patron’s doubt on new technology and less demand on using them in house-keeping library operation.